2004
DOI: 10.1111/j.1464-5491.2004.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

The post‐prandial state in Type 2 diabetes and endothelial dysfunction: effects of insulin aspart

Abstract: This study shows that the post-prandial state is accompanied by endothelial dysfunction in Type 2 diabetic patients and that insulin aspart improved endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 32 publications
4
54
0
1
Order By: Relevance
“…Postprandial hyperglycemia has been shown to be closely related with cardiovascular disease, [13] aggravation of oxidative stress and endothelial dysfunction. [14,15] The high frequency of hyperglycemic events in our study is consistent with other studies [7,9,16] and indicates that relying on only HbA1c in the management of diabetes (as is being advised presently) is inadequate for reducing the rate of cardiovascular complications. Another primary outcome of our study was to detect hypoglycemia in well-controlled patients.…”
Section: Discussionsupporting
confidence: 89%
“…Postprandial hyperglycemia has been shown to be closely related with cardiovascular disease, [13] aggravation of oxidative stress and endothelial dysfunction. [14,15] The high frequency of hyperglycemic events in our study is consistent with other studies [7,9,16] and indicates that relying on only HbA1c in the management of diabetes (as is being advised presently) is inadequate for reducing the rate of cardiovascular complications. Another primary outcome of our study was to detect hypoglycemia in well-controlled patients.…”
Section: Discussionsupporting
confidence: 89%
“…Ceriello and coworkers (2002) showed that targeting postprandial hyperglyaemia has the potential to reduce oxidative stress (by reducing peroxynitrite production) [55]. The short-acting insulin analog insulin aspart reduced oxidative stress and improved endothelial function more effectively than the slower-acting regular insulin [55,56]. A placebo-controlled study focusing on reducing postprandial hyperglyaemia in patients with type 2 diabetes with acarbose found reduced activation of the transcription factor nuclear factor-kappa, which is known to have a central role in the pathogenesis of arteriosclerosis [57].…”
Section: Oxidative Stressmentioning
confidence: 98%
“…This study provides an alternative natural product from seagrass with hyperbolic potency and lesser side effects than present synthetic drugs. The inhibition of α-amylase and α-glucosidase may lead to reduction in postprandial hyperglycemia which is an important risk factor for cardiovascular diseases [17]. Thus, the inhibition of α-amylase and α-glucosidase is important to control post-postprandial hyperglycemia in the treatment of diabetes.…”
Section: Discussionmentioning
confidence: 99%